Mullerian adenosarcoma (heterologous) of uterine cervix with sarcomatous overgrowth: A case report with review of the literature - Debahuti Mohapatra; Pranita Mohanty; Rupanita Biswal (Wolters Kluwer Medknow Publications, 2019)
Mullerian adenosarcoma is a rare biphasic malignant neoplasm of cervix characterized by an admixture of benign epithelial elements and a malignant sarcomatous stromal component, which may be either homologous or heterologous. Mullerian adenosarcoma with stromal overgrowth (MASO) in an aggressive variant of adenosarcoma, which is extremely rare with only two such cases reported till date. In this report, we present a case of MASO of cervix with heterologous elements in a 55/F presenting with postmenopausal bleeding. As it commonly simulates clinically and radiologically as benign cervical polyp, the gynecologists and pathologists should be aware of this extremely rare entity presenting with aggressive clinical course.